2014
DOI: 10.1002/ange.201402254
|View full text |Cite
|
Sign up to set email alerts
|

The Compressibility of pH‐Sensitive Microgels at the Oil–Water Interface: Higher Charge Leads to Less Repulsion

Abstract: pH-responsive microgels are unique stabilizers for stimuli-sensitive emulsions that can be broken on demand by changing the pH value. However, recent experiments have indicated that electrostatic interactions play a different role to that in conventional Pickering emulsions. The influence of charges on the interactions between microgels at the oil-water interface is now described. Compression isotherms of microgels with different charge density and architecture were determined in a Langmuir trough, and counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(90 citation statements)
references
References 37 publications
4
86
0
Order By: Relevance
“…Several studies have focused on the spontaneous adsorption of microgels in model geometries, using particle tracking techniques at a flat interface 21,22 , the pendant drop method 5,[22][23][24][25][26] or Langmuir trough experiments [25][26][27] . Interestingly, particle tracking studies performed recently showed that the particles eventually form clusters 20,21 , the origin of which is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have focused on the spontaneous adsorption of microgels in model geometries, using particle tracking techniques at a flat interface 21,22 , the pendant drop method 5,[22][23][24][25][26] or Langmuir trough experiments [25][26][27] . Interestingly, particle tracking studies performed recently showed that the particles eventually form clusters 20,21 , the origin of which is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The surface activity of the co-polymers in the microgel is in fact a very weakly varying function of pH between 3 and 9, which is the experimentally relevant window. Conversely, the mechanical response of microgel monolayers upon compression varies at different values of pH within the same window, highlighting the complex interplay between the different particle properties 43 . To fix the experimental conditions, all the experiments reported in this paper were performed using microgel dispersions in Milli-Q water.…”
Section: Two-dimensional Phase Diagrams: Compression and Depositionmentioning
confidence: 99%
“…In particular, the existence of both shell-shell and core-core contacts has been assumed, but to date, a systematic visualization of these structures and a thorough study on the transitions between them is still lacking. Additionally, measurements of compression isotherms showed a counterintuitive response in the presence of bulk charges in the microgels, with uncharged particles interacting via the interface at larger inter-particle separations compared to charged systems 43 . Furthermore, dilatational elasticity showed an unexpected non-monotonic behavior of the elastic modulus with compression of interfacial microgel monolayers, suggesting that the presence of coreshell interactions couples non-trivially to the interface structure and mechanical properties 42,44,45 .…”
Section: Introductionmentioning
confidence: 99%
“…Microgels exhibit interesting properties that lie between linear polymers and three-dimensional polymer networks (hydrogels). [1][2][3][4][5][6] Stimuli-responsive microgels can undergo changes in size, softness and surface charge by varying pH, light, solvent or temperature. [7][8][9][10][11] The modification of microgels with metal or metal oxide nanoparticles, ions or proteins results in new materials with enhanced properties.…”
mentioning
confidence: 99%